Sentidos de participação e autoridade: um olhar sobre uma experiência comunitária - Terahata, Adriana Miritello (2008)
This thesis looked into revealing how authority and participation are understood by educators and youths of educational projects developed in a suburban community in Sao Paulo. The purposes were to provide considerations about the meaning of authority and participation in the educative situation studied and, by means of providing constructed and systematized knowledge, contribute to dialogic and participative educational practices. When seeking such meanings, I tried to understand how such experiences work, instead of the concepts or definitions. I performed this search by means of interviews with educators and some youths participating in the projects and of interlocution with the work of Hannah Arendt. For the author, the responsibility for the world assumes the shape of authority, which results from the fact that the educator knows the world and is able to teach others about it; the author also states that we can destroy all that by molding the youths. From that situation, a challenge is born for the educational practice: presenting an existing world exercising authority and guaranteeing the new one that the youngster brings within; what can take place by means of participation experiences. Both the participation experience and the authority have close meanings for educators and youths. In the speech, there is a clear difference between authority (which dialogues) and authoritarian (which demands), but when describing the practice, the difference turned out to be subtle. Regarding the meaning of participation, a similar movement occurred, for the reason that when they described their thoughts on that matters, it was outlined the possibility of change of an unfair reality, but when the practice was described, the experiences brought were centered in the performance of home tasks. In both cases, the revealed meaning was related to personal life. Taking into account such elements, this paper tried to challenge the reader to think the participation of youths from this point of view: it can only be possible in a relation in which the reference of the adult authority is made present. And this presence is not linked to disciplinarian power, but to a work of listening and welcoming of the youths, since the adult-youth relation is asymmetric, demanding protection and respect